Clinical FDG‐PET Findings in Patients with Temporal Lobe Epilepsy: Concordance with EEG and MRI. Issue 1 (29th October 2019) - Jaisani, Zeenat; Miletich, Robert S.; Ramanathan, Murali; Weinstock, Arie L.
ABSTRACT: BACKGROUND AND PURPOSE: We aimed to study the yield of PET in temporal lobe epilepsy (TLE) by analyzing the correlation of PET findings with MRI, and interictal and ictal EEG findings, in a single‐center cohort of patients with TLE. Predictors of PET thalamic changes and its role in predicting postsurgical outcome were also studied. METHODS: This was a retrospective study of 39 patients with TLE who underwent MRI, PET, and scalp video EEG monitoring at the University at Buffalo, New York from 2001 to 2011 during presurgical evaluation. PET‐defined metabolism of the temporal lobes was evaluated using a 4‐point ordinal rating scale. RESULTS: PET hypometabolism was associated with a variation in ictal ( P = .034) and interictal ( P  < .001) foci in both lesional (by MRI) and nonlesional patients. Nonlesional MRI scans were associated with none to mild temporal PET hypometabolism (71% of patients) while lesional MRI scans were associated with moderate to severe hypometabolism (82% of patients) ( P = .006). The odds of thalamic hypometabolism were 5.36 times higher when there was moderate to severe temporal hypometabolism ( P = .039). CONCLUSION: This study underscores the utility of PET in localizing ictal foci in TLE patients even in those with normal MRI. The degree of PET hypometabolism corresponds to presence of MRI pathology. Coexistent thalamic hypometabolism with temporal hypometabolism suggests a secondary effect of distant temporal network disruption. Extratemporal metabolism is a predictor of poor postsurgical seizure outcome in TLE patients.